Cortical Electrical Stimulation Ameliorates Traumatic Brain Injury-Induced Sensorimotor and Cognitive Deficits in Rats - Kuo, Chi-Wei; Chang, Ming-Yuan; Liu, Hui-Hua; He, Xiao-Kuo; Chan, Shu-Yen; Huang, Ying-Zu; Peng, Chih-Wei; Chang, Pi-Kai; Pan, Chien-Yuan; Hsieh, Tsung-Hsun (Frontiers in Neural Circuits, 2021)
Objective: Individuals with different severities of traumatic brain injury (TBI) often suffer long-lasting motor, sensory, neurological, or cognitive disturbances. To date, no neuromodulation-based therapies have been used to manage the functional deficits associated with TBI. Cortical electrical stimulation (CES) has been increasingly developed for modulating brain plasticity and is considered to have therapeutic potential in TBI. However, the therapeutic value of such a technique for TBI is still unclear. Accordingly, an animal model of this disease would be helpful for mechanistic insight into using CES as a novel treatment approach in TBI. The current study aims to apply a novel CES scheme with a theta-burst stimulation (TBS) protocol to identify the therapeutic potential of CES in a weight drop-induced rat model of TBI. Methods: TBI rats were divided into the sham CES treatment group and CES treatment group. Following early and long-term CES intervention (starting 24 h after TBI, 1 session/day, 5 days/week) in awake TBI animals for a total of 4 weeks, the effects of CES on the modified neurological severity score (mNSS), sensorimotor and cognitive behaviors and neuroinflammatory changes were identified. Results: We found that the 4-week CES intervention significantly alleviated the TBI-induced neurological, sensorimotor, and cognitive deficits in locomotor activity, sensory and recognition memory. Immunohistochemically, we found that CES mitigated the glial fibrillary acidic protein (GFAP) activation in the hippocampus. Conclusion: These findings suggest that CES has significant benefits in alleviating TBI-related symptoms and represents a promising treatment for TBI.